The interface between western and indigenous signs in Zanu-PF advertisements for July 2013 elections - Chibuwe, Albert (Communicatio South African Journal for Communication Theory and Research, 2020)
Political contestation in Zimbabwe post-2000 has been largely acrimonious. In the electoral domain of the epoch, political advertising, has been one of the key tools through which this contestation took place. However, these advertisements have been barely studied and those that have made an attempt to study them did not examine them from advertising theory and/or sign theory perspective. The study argues that locating the analysis of political advertisements in advertising theory and sign theory presents an opportunity to gain insights into how political products gain sign value, exchange value and utility value. The study deploys advertising theory and sign theory to examine the value that selected indigenous and Western signs used by the Zimbabwe African National Union-Patriotic Front (ZANU-PF) invest in the political products: ZANU-PF and Mugabe. By interrogating four purposively selected signs in ZANU-PF advertisements for the July 2013 elections, I seek to establish how political products are produced as signs and signs as political products. The selected signs are subjected to semiotic analysis. The findings show that ZANU-PF's use of these valorised Western and indigenous, often contradictory, signs is designed to appeal to votes on the basis that it is a democratic, divine anointed, Christian and African-oriented party.